THE ROLE OF EDUCATIONAL INSTITUTIONS IN FORMING LEARNED CHARACTER - Zamroni, Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Character becomes important in a person's life, because the character becomes one of the determinants of one's success. Therefore, a strong and positive character needs to be formed well. Education is not only enough to make children smart, but also must b able to create noble values or character. A person's success is not determined solely by knowledge and technical abilities only, but more by the ability to manage themselves and others (soft skills). the character of Indonesian society has not been in according with the ideals of the nation. The factors that cause the nation's low character are: (1) the education system places less emphasis on character building, but more emphasis on intellectual development, (2) environmental conditions that do not support development of good character. Formation characters, especially students become urgent and urgent to immediately realized in order to create a better society, namely society can face regional and global challenges. Regional and global challenges in question is how our young generation not only has the academic abilities focused on cognitive abilities only, but also affective and moral aspects touched. On the other hand the values and spirit of the nation and state can be an inspiration for strengthening the identity of the nation's character education in the faces of multidimensional crisis. Education US a the totality of effort and action must be carried out through three educational institutions that are, Family, School and community. Therefore, integration is required Board of Family Education, school education and Community Education Board in conducting character education. Strengthening the three educational institutions shows that character education is necessary in order to anticipate the problems of the futures are becoming more complex.